PENGALAMAN GAME YANG MENYENANGKAN UNTUK MENGIDENTIFIKASI TIPE DUNIA METAVERSE SEBAGAI MODEL PEMBELAJARAN YANG INOVATIF - Sulistianingsih AS; Mojibur Rohman; Purnomo; Eddy Sutadji (Steam Engineering, 2022)
Metaverse aims to turn imagination into reality through the convergence of different technologies and should be seen as a means of lifelong learning that is not limited in space and time. The aim of this research is to identify the type of world in the metaverse to provide a pleasant user experience. The research method used in this research is descriptive qualitative. In this study, the data collection method used is the study of documentation and literature. Literature study is carried out by searching for various written sources, both in the form of books, archives, magazines, articles, and journals, as well as documents that can assist writers in exploring the types of games in the virtual metaverse world that support online learning. The results of this study can be used by educators to create an innovative learning environment, so that it can provide equal learning opportunities for all students.